1998
DOI: 10.1046/j.1365-2400.1998.550383.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring warm‐water fish populations in north temperate regions: sampling considerations when using proportional stock density

Abstract: Three lakes were repeatedly sampled at night using boat electric fishing, experimental gill netting, and fyke netting from May to November 1993 to evaluate the feasibility of using proportional stock density (PSD) to monitor warm‐water fish populations in Washington State, USA. Additionally, average night‐time boat electric fishing catch‐per‐effort of largemouth bass, Micropterus salmoides (Lacepéde), from 30 Washington lakes was also analysed to determine the amount of effort required to obtain adequate sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Logistics often restrict sampling to daytime hours only, and this is probably appropriate for general monitoring studies of riverine fishes across large geographic areas. In circumstances where a more detailed understanding of fish assemblages is required at specific sites, such as in designing fishways or other types of habitat restoration measures, however, night‐time sampling may provide valuable additional data (Divens et al , 1998). Before commencing fish passage improvement programmes, it would be useful to conduct a pilot study incorporating night sampling (and possibly also additional gear types) to assess the potential for bias arising from diel changes in abundance and size structure.…”
Section: Discussionmentioning
confidence: 99%
“…Logistics often restrict sampling to daytime hours only, and this is probably appropriate for general monitoring studies of riverine fishes across large geographic areas. In circumstances where a more detailed understanding of fish assemblages is required at specific sites, such as in designing fishways or other types of habitat restoration measures, however, night‐time sampling may provide valuable additional data (Divens et al , 1998). Before commencing fish passage improvement programmes, it would be useful to conduct a pilot study incorporating night sampling (and possibly also additional gear types) to assess the potential for bias arising from diel changes in abundance and size structure.…”
Section: Discussionmentioning
confidence: 99%
“…The SGPL was developed using information obtained from (1) previous sampling guidelines for Washington (Zook 1978;Fletcher et al 1993), (2) two short courses on warmwater fisheries and standardized sampling provided by outside experts (William Davies and David Willis), (3) intensive literature searches, (4) studies comparing warmwater sampling techniques conducted in Washington (Fletcher et al 1993;Divens et al 1998), (5) personal communication among warmwater field biologists in Washington, and (6) communications with warmwater fisheries experts outside of Washington. The SGPL was developed using information obtained from (1) previous sampling guidelines for Washington (Zook 1978;Fletcher et al 1993), (2) two short courses on warmwater fisheries and standardized sampling provided by outside experts (William Davies and David Willis), (3) intensive literature searches, (4) studies comparing warmwater sampling techniques conducted in Washington (Fletcher et al 1993;Divens et al 1998), (5) personal communication among warmwater field biologists in Washington, and (6) communications with warmwater fisheries experts outside of Washington.…”
Section: Important Considerations When Developing Standardized Procedmentioning
confidence: 99%
“…Divens et al (1998) identified sampling equipment that maximized C of common warmwater sport fishes in Washington, as did information from the literature (e.g., Bagenal 1978;Sigler and Sigler 1990;Murphy and Willis 1996). Divens et al (1998) identified sampling equipment that maximized C of common warmwater sport fishes in Washington, as did information from the literature (e.g., Bagenal 1978;Sigler and Sigler 1990;Murphy and Willis 1996).…”
Section: Important Considerations When Developing Standardized Procedmentioning
confidence: 99%
“…Thus, it may be easier to collect a sufficient sample size for a given degree of precision than for indices such as PSD and RSD. For example, in 30 night electrofishing surveys in Washington State, an average of 26 stock-length fish were caught per hour, and an average of 1.02 h of pedal-down electrofishing time was used per night (Divens et al 1998). Therefore, on average, 2.07 nights of electrofishing would have been required to capture the 55 largemouth bass larger than 200 mm that would be necessary to ensure a PSD estimate of Ϯ10 with 80% confidence (Gustafson 1988;Divens et al 1998).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Even for sport fish populations, information provided by current stock density indices is often not enough. In some systems, obtaining the necessary sample size for precise estimates of PSD or RSD can be difficult because of low catch rates of stock size and larger fish (Serns 1985;Divens et al 1998). A method with the option to incorporate a greater proportion of the length-frequency distribution of fish from these systems, such as fish smaller than stock length, would increase sample size and statistical power.…”
mentioning
confidence: 99%